2011
DOI: 10.1071/en11033
|View full text |Cite
|
Sign up to set email alerts
|

1-D and 2-D NMR metabolomics of earthworm responses to sub-lethal trifluralin and endosulfan exposure

Abstract: Environmental contextEnvironmental metabolomics is an emerging field that examines the metabolic changes in organisms in response to potential environmental stressors. In this study, nuclear magnetic resonance spectroscopy is used to investigate earthworm metabolic responses to sub-lethal exposure of environmentally persistent pesticides. The study identifies two toxic modes of action elicited by the pesticides, and highlights the potential of metabolomics for the chemical assessment of persistent environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 74 publications
1
28
0
Order By: Relevance
“…In addition, t-test filtered 1 H NMR difference spectra were also used in an exploratory capacity to identify metabolites that increased or decreased significantly (at α¼0.05) relative to the controls (Supplementary Material, Figs. S3 and S4;Ekman et al, 2008Ekman et al, , 2009Yuk et al, 2011). Table 1 lists the metabolites that significantly fluctuated in their concentrations in response to C 60 nanoparticle exposure as identified by the PCA loadings plots and the t-test filtered 1 H NMR difference spectra (Supplementary Material, Figs.…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, t-test filtered 1 H NMR difference spectra were also used in an exploratory capacity to identify metabolites that increased or decreased significantly (at α¼0.05) relative to the controls (Supplementary Material, Figs. S3 and S4;Ekman et al, 2008Ekman et al, , 2009Yuk et al, 2011). Table 1 lists the metabolites that significantly fluctuated in their concentrations in response to C 60 nanoparticle exposure as identified by the PCA loadings plots and the t-test filtered 1 H NMR difference spectra (Supplementary Material, Figs.…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
“…They showed that only cocoon production was significantly hindered and this was also only at the highest exposure concentration of 50,000 mg/kg, which is markedly higher than any reported environmental concentrations. Therefore, their conclusions that C 60 nanoparticles are not acutely toxic to E. fetida need to be further explored at lower concentrations as studies with other environmental contaminants have reported significant metabolite fluctuations with sub-lethal exposure (Brown et al, 2010;Lankadurai et al, 2011b;McKelvie et al, 2011;Mosleh et al, 2003;Neuhauser and Callahan, 1990;Yuk et al, 2011). Metabolomic methods can also aid in elucidating the biochemical mode of action (MOA) of contaminant exposure.…”
Section: Introductionmentioning
confidence: 99%
“…For Organochlorine pesticides is reported the inhibition of neurotransmitter GABA that produces a decrease uptake of chlorine ions in neurons, resulting in partial repolarization and leads convulsions and muscle contractions in organisms (40)(41)(42)(43)(44). For Organophosphate and Carbamate have similar behavior.…”
Section: Modes and Mechanisms Of Actionmentioning
confidence: 99%
“…Environmental metabolomics studies are focused on the metabolic changes that occur in organisms in response to an exposure event or environmental stress (20,(59)(60) and bioavailability studies using metabolomics are focused on monitoring biochemical markers that explain the presence or absence of xenobiotics in the environment. In many cases, these compounds undergo transformation and degradation, which is why they may not be found in their original form or in their environmental matrix as soil, water, plants, air and so on.…”
Section: Environmental Metabolomics and Bioavailabilitymentioning
confidence: 99%
“…Although the acute health effects of these xenobiotics are well documented, the effect of chronic exposure remains an open question [1-3, 5, 6]. The intrinsic interactions between these xenobiotics and soils hold the key to understanding both their environmental accumulation and their bioavailability [7][8][9][10][11]. Therefore, a better understanding as to how xenobiotics are sequestered into complex rock, soil, and sediments is required [12][13][14].…”
Section: Introductionmentioning
confidence: 99%